Simulation of the mechanical behavior of osteons using artificial gravity devices in microgravity. Issue 14 (10th November 2021) - Zhang, Hao; Liu, Hai-Ying; Zhang, Chun-Qiu; Liu, Zhen-Zhong; Wang, Wei
Abstract: Aviation medical research shows that disuse osteoporosis will occur after long-term space flight. Even with countermeasures such as exercise and drug treatments, this outcome cannot be avoided in flight. In recent years, the application of artificial gravity devices that change the mechanical microenvironment of bone in microgravity have shown promise in mitigating the risk of disuse osteoporosis. Considering the existence of osteocytes, a fluid-solid coupling finite element model for osteons with two-stage pore structure (Haversian canal, lacunar-canalicular system) was established. In order to study the changes in the mechanical behavior of osteocytes under the action of various artificial gravity (AG) devices, including long-arm centrifuge (LAC), short-arm centrifuge (SAC), and a lower body negative pressure (LBNP) chamber. In addition, the difference in pulsating pressure and static pressure stress caused by the gravity gradient under the AG devices was examined. The simulation results showed that the AG devices could effectively improve the stress level of osteocytes in microgravity. The mechanical microenvironment of osteocytes that was provided by the LAC was closest to that of the Earth' s gravitational field. The mechanical stimulation on osteocytes was not significantly improved by the SAC, but from a practical viewpoint, it occupied less space than the LAC. The LBNP chamber created a higher level of stress for osteocytes. Therefore, the LAC was an ideal device for replacing Earth' s gravitational field, except for the practical limitations of its physical size. In contrast, the LBNP device had the greatest application potential in training for its expansibility and convenience.